Cosa è esterno alla mente stoica? - Alessandrelli, Michele (Peitho. Examina Antiqua, 2024)
This paper explores the role of external factors in the constitution of the Stoic mind. It will show how the external influences the Stoic mind in several crucial ways: 1) Constitutive Role: The external world acts as a constitutive factor for the soul (the third level of the scala naturae), shaping its development. At the fourth level, the logos (rational principle) interacts with qualified external objects. These objects form the basis of abstract reasoning and teachings derived from external sources; 2) Truth-Making Function: The external world serves as a truth-maker for phantasiai and the axiomata associated with them, providing validation and substance to internal representations and core beliefs; 3) Opposition to External Goods: For the Stoic soul dedicated to virtue, external goods are elements to be opposed or transcended. The Stoic perspective emphasizes the pursuit of virtue as independent of external goods, which are considered indifferent or secondary to moral development; 4) Condition of Possibility: the external void or incorporeal space is a necessary condition for the growth of the cosmos, including its periodic conflagration (destruction) and subsequent reconstitution.